Analyzing the Translation of the Part-speech “wa low tara ez” Based on Pragmatics: : A Case Study of Surah Mubaraka An’am - divsalar, Farhad; Pouya, Masumeh (Iranian Journal of Translation Studies, 2023)
Pragmatics is an interdisciplinary science that studies the hidden meanings behindwords, it also reflects and is precise in defining the relationship of the structure of a text in order to properly navigate the process of finding the meaning behind it. The Holy Qur’an is one of the important texts in which understanding the precise meaning and transferring it to non-Arab readers is very important and has always been the focus of researchers and translators. Therefore, it is necessary to use different tools for accurate understanding and translation. Translation of tamani customs, especially the letter “low” is one of the most challenging cases in the Holy Quran. Translators have differences in the translation of the “Va low tara ez” verse which is mentioned seven times in the Holy Quran. Due to the fact that this verse is used three times in the Surah Mubaraka An’am, therefore, the study of this surah is the focus of this research. This research tries to analyze this Quranic discourse by relying on pragmatics and speech act theory. The researchers can identify the appropriate meaning of these verses by considering the context of the rest of the verses and speeches؛ and in the course of the research, introduce the translators who translated with this point of view. The research method is in the form of text analysis based on analysis, description, comparison and presentation of statistics. The result of the research indicates that out of seventy Persian translations, only 22% of verse 27, 12% of verse 30, and 27% of verse 93 of Surah An’am have been translated in tamani form, However, due to the high frequency of persuasive actions in these verses, perceiving the serious meaning of said verses is realized by considering the letter “Low” to be in tamani form.